THE EFFECTIVENESS OF INSTAGRAM WRITING COMPARED TO TEACHER CENTERED WRITING TO TEACH RECOUNT TEXT TO STUDENTS WITH HIGH AND LOW MOTIVATION (The Case of Eight Grade Students in SMP Kesatrian 1 Semarang in the Academic Year of 2015/2016) (ELT Forum: Journal of English Language Teaching, 2016)
This final project is based on a study which attempts to examine the effectiveness of instagram writing compared to teacher centered writing to teach recount text to students with high and low motivation of SMP Kesatrian 1 Semarang in the academic year of 2015/2016. This final project has several objectives; to measure how effective instagram writing is to teach recount text to students with high motivation, to measure how effective instagram writing is to teach recount text to students with low motivation, to measure how effective teacher centered writing is to teach recount text to students with high motivation, to measure how effective teacher centered writing is to teach recount text to students with low motivation and to measure how effective instagram writing is compared to teacher centered writing to teach recount text to students with high and low motivation. This study was conducted by using Experimental research with 40 students participated. Those students were divided into experimental and control group. The experimental group was taught writing recount text by using instagram as a teaching technique, whereas the control was taught by using teacher centered writing. Results indicated that the final average score of experimental group was 73. Meanwhile, the control group got a lower average score with 67.15. After calculating the significance of the test, the result of the t-value was 2.210 and t-table was 2.002. With regard to the previous results, it can be concluded that teaching recount text using instagram resulted a better achievement. Besides, the t-value of the post test was higher than the critical value which meant that the difference was statistically significant. Thus, the higher achievement of experimental group indicated that the use of instagram promoted a better understanding for students with high and low motivation which improved the quality of their writing.